Medical Team Support for Table Tennis Event – LPTK CUP XXI UM 2023 - Ramadhan, Muhammad Putra; Sishartami, Lintang Widya; Aditya, Ronal Surya; Rahmatika, Qory Tifani; Sunaryo, Eri Yanuar Akhmad Budi; Evi, Nurul; Masfi, Achmad; Afiani, Nurma; Widjayanti, Yhenti (Inovasi Lokal, 2023)
Introduction: LPTK CUP strives to improve relationships and unity among LPTK (Lembaga Pendidikan Tenga Kependidikan) members. It achieves this by merging competitive elements with entertainment to promote a feeling of camaraderie and cooperation. Furthermore, LPTK CUP includes a range of sports competitions, including table tennis. Purpose: This study aims to comprehend the medical team's involvement in providing support during the table tennis event at LPTK CUP XII UM 2023. Method: The medical team is crucial in delivering general and specialized healthcare services (for sports injuries) throughout the table tennis competition at LPTK CUP XXI UM 2023. Additionally, various approaches are employed in this event, including 1) Acquiring Medical Equipment, 2) Collaborating with Relevant Entities, 3) Arranging the Placement of the Medical Team, 4) Conducting Screening and Medical Services, and 4occurredviding Health Education. Result: Most table tennis participants are less than 50 years old. Several injuries occur during the match, namely Abrasion, Shoulder Sprain, and Ankle Sprain. The injury management provided is based on the Rice Method for sports injuries.